2006
DOI: 10.1055/s-2006-931582
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Steroidal Saponins from Smilax medica

Abstract: Two new spirostanol saponins ( 1 and 2) were isolated from the roots of Smilax medica, together with the known smilagenin 3-O-beta-D-glucopyranoside (3). Their structures were determined by spectroscopic methods including 1D- and 2D-NMR experiments. Compounds 1 and 2 exhibited antifungal activity against the human pathogenic yeasts Candida albicans, C. glabrata and C. tropicalis (MICs between 6.25 and 50 microg/mL) whereas 3 was inactive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Plants produce metabolites with antimicrobial properties when they have been exposed to microorganisms. The antifungal activity of essential oils [17,18], saponins [19] and some alkaloids [20] has already been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Plants produce metabolites with antimicrobial properties when they have been exposed to microorganisms. The antifungal activity of essential oils [17,18], saponins [19] and some alkaloids [20] has already been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, many Smilax species from other parts of the world such as Smilax china have been submitted to numerous chemical and biological studies due to their interesting properties. These species have been shown to contain steroidal saponins and phenolic compounds Sashida et al, 1992;Bernardo et al, 1996;Shu et al, 2002;Sautour et al, 2006;Xu et al, 2006) and have demonstrated interesting anti-inflammatory, anti-conceptive, cytotoxic, antioxidant, immunomodulatory, anticancer, hypoglycaemic, uricosuric and antifungal activities (Giachetti et al, 1988;Suh et al, 1996;Fukunaga et al, 1997;Lee et al, 2001;Jiang and Xu, 2003;Cox et al, 2005;Kuo et al, 2005;Sautour et al, 2005;Thabrew et al, 2005;Xu et al, 2005;Chu and Ng, 2006;Huang et al, 2006;Wang et al, 2006;Li et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous observations, saponins having a furostan skeleton (2, 4, 5, 6) were devoid of activity against the tested fungi. 5,6,[10][11][12] Concerning the spirostanol saponins, only compound 3, having two sugars for the osidic chain showed an antifungal activity against the yeast tested with minimum inhibitory concentration (MIC) values between 25 and 50 mg/ml (Table 4). Antifungal activities were also observed previously with SS 1 which differ of 3 by the (1→6) linkage of the second glucose.…”
Section: C-nmr Shift Of 25r-spirostanes (D C 171-172)mentioning
confidence: 99%
“…5,6) As part of our ongoing search for new antifungal steroid saponins, 5,6,[10][11][12] we have investigated the roots of Smilax aspera subsp. mauritanica.…”
mentioning
confidence: 99%